PEMBERIAN ANOMALI KEDALAMAN REFLEKTIF PADA SIMULASI PERSAMAAN AIR DANGKAL DENGAN KONFIGURASI SEJAJAR - Pramono, Nugroho Adi (Sainstek : Jurnal Sains dan Teknologi, 2016)
The simulation of shallow water equation with straight configuration reflective depth anomaly has been performed. This program simulated wave absorber in the beach in order to prevent furthur abrasion of by sea. This program using modified Navier-Stokes equation and running on Matlab program. The result show that depth-anomaly reduced the amount on wave amplitudo by significant value.